教育輿情中的教育政策目標, 議題關注與價值表達: 以兩份十大教育新聞榜單的話語分析為例 - 陳霜葉; 孟瀏今 (北京大學教育評論, 2014)

Implementation of Enterprise Resource Planning for the Supply Chain Management of the Food and Beverage Department at Macao Entertainment Corp - Vai, Fong Tou; Lee, Leanda; Negreiros, Joao (Information Resources Management Journal (IRMJ), 2014)
One of the six gaming concession holders in Macao, Macao Entertainment Corp (MEC)1, undertook to centralize three casino/entertainment properties through utilization of a centralized Enterprise Resource Planning (ERP) in April 2010. The Supply Chain (SC) department was the first to apply the ERP in...

Lugares da Memória, Representações e Poderes - Simões, José Manuel da Silva (Rizoma, 2014)
No seguimento de uma série de contactos estreitos com uma comunidade social situada nos municípios de Baía da Traição, Rio Tinto, Marcação e Mataraca, a 85 quilómetros de distância de João Pessoa, capital do Estado da Paraíba, decidi, desde 2006, levar a efeito um intenso trabalho de campo nestas aldeias indígenas com o objectivo de concretizar um projeto de investigação que englobasse em obrigatória interdisciplinaridade os campos tantas vezes excessivamente singulares da História, da Sociologia, da Política, da Antropologia Cultural e das Teorias da Comunicação, acompanhando e refletindo sobre características e organização social, rituais, manifestações de carácter religioso, evolução histórica, usos e costumes de uma tribo que se abriu quase rendida ao exterior, mas porfiando em manter, todavia, traços e, sobretudo, um discurso narrativo de representações culturais ancestrais. Esta propositada interdisciplinaridade persegue um objectivo epistemológico bem preciso: transformar a investigação empírica em contribuição para uma nova teoria da história da comunicação – a comunicação antropo-histórica entre comunidades ditas tradicionais e o “outro” – a área por mim privilegiada em investigações anteriores, nomeadamente ao nível da licenciatura e do mestrado. Os Potiguara, cuja sociedade ainda não é alfabetizada e, na sua maioria, baseiam a sua cultura na tradição oral, transmitindo os seus lugares da memória sobretudo através do poder do português do Brasil, mesmo quando adornado por escassas palavras tupi, é graças à mensagem e à representação que algumas das suas manifestações culturais reinventam continuadamente a sua identidade Potiguara. É, assim, a mensagem e a representação que inventam o real social e reinventam dinamicamente a sua identidade cultural.
Keywords: Lugares de Memória

Personality and learning styles surrounded by W3 software: The Macao Portuguese school case - Negreiros, João; Baptista, Zelia; Lee, Leanda (Education and Information Technologies, 2014)
One of the purposes of this study is to evaluate how the choice of teaching method can be assisted by knowledge of a student’s personality type and learning style. The present research is undertaken in the context of Web 2.0 tools use within the Portuguese literature subject at Escola Portuguesa de Macao (EPM). The Felder-Soloman index of learning style (ILS) and the Myers-Briggs Type Indicator (MBTI) based upon Jung’s theory of psychological nature were used as measures of learning style and personality type with 8th grade EPM students. Descriptive and chi-squared correlation statistical results of the associations between personality and learners types are presented. These results are discussed positing that the knowledge of student’s personality traits and learning styles together may have a notable implication for teaching methods.
Keywords: Escola Portuguesa de Macao (EPM); Felder and Soloman; ILS; MBTI; Myers and Briggs; Web 2.0

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

African Female Nascent Entrepreneurship In The Macao S.A.R. - Morais, Isabel (Urban Anthropology and Studies of Cultural Systems and World Economic Development, 2014)
African women from different countries and social classes, from those seeking refugee status to diplomats and peasants' daughters, have been arriving in increasing numbers on Chinese shores since the 1980s. The amazing stories of some of these "invisible" but dynamic women have been ignored, yet they reveal great diversity and deserve scholarly attention, as they provide rich material for studies on the African diaspora in China. This article focuses on African migration to Macao, a former Portuguese colony and primary migration destination in the Pearl Delta River Region, which currently hosts the densest African population in China. It explores both the more recent and the relatively longer-term migration of African women and university students to Macao, and examines the intersection of these communities resulting from the overlap between the ongoing global movements of African diasporas and new African migratory trends to China. The article draws on the life stories as well as the educational and entrepreneurial experiences of African women in Macao, and investigates the relevance of ethnic networks of trust and reciprocity for their communities' survival. This article places specific emphais on the experiences of African women, recognizing their achievements in the face of multiple intersections of racism and sexism on the part of both state and society, and reveals how the women employ a resistance strategy by reinforcing ethnic migrant networks.

Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

The other side of creative industries in Hong Kong and Macau - Mendes, Carla de Utra; Simoes, José Manuel (International Journal of Cultural and Creative Industries, 2014)

Alternative pathway history in a fish with plastic reproductive tactic - Gonçalves, David (Functional Ecology, 2014)

Oestradiol and prostaglandin F2α regulate sexual display in female of a sex-role reversed fish - Gonçalves, David (2014)

Capture and transformation of urban soundscape data for artistic creation - Gomes, Jose Alberto; Pinho, Nuno Peixoto De; Lopes, Filipe; Costa, Gustavo; Dias, Rui; Tudela, Diogo; Barbosa, Álvaro (Journal of Science and Technology of the Arts, 2014)

An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

Researching international student migration in Asia: research design and project management issues - Ge, Yun; Ho, Kong Chong (Journal of Population Research, 2014)
In the context of Asia, the changing dynamics of higher education has increased the visibility and significance of the group of intraregional education migrants. There are several methodological issues which need to be addressed in conducting research for this group of migrants. First, how does the particular type of migrant group and Asian context influence the research design? Second, in order to capture the scale and diversity of this migrant group, how should research be conducted across multiple sites? Third, how does a mixed method design allow researchers to learn more about the behaviour, practice and orientations of education migrants? Our paper aims to make contributions to the discussions on the methods of education migration research in Asia through answering these questions. We use research experiences and preliminary data from a multinational project to illustrate the issues involved in the selection of methods, research design and project management.
Keywords: Asia; Higher education; International student migrants; Mixed methods; Multi-site design; Multicultural research

Privacy in sound-based social networks - Cordeiro, J.; Barbosa, A. (Communications in Computer and Information Science, 2014)

The creative industries as an integrated factor in a sustainable model for Macao's economic development - Azevedo, Margarida; Barbosa, Álvaro (Creative Industries Journal, 2014)
This article presents an insight into one of the regions with the fastest-growing economy, heavily based on an entertainment, gaming and tourism industry, and that is urgently looking for a sustainable model that articulates with complementary sectors within the cultural and creative industries – Macao. Macao is facing a major economic and social challenge; it has grown as a vulnerable economy relying almost exclusively on gaming revenues. Alternative activities to diversify the economy are urgently required to answer the competition risks haunting this industry. The cultural and creative industries could be a complementary activity – a vehicle for economic diversification. However, current public and private stakeholders for the cultural and creative sector might have been neglecting the unique cultural and heritage ecosystem of the territory, focusing on isolate opportunities and overlooking an inclusive and robust strategy. A sustainable model that attends to the local conditions and its people is required for alternative activities to become a meaningful sector for the social and economic development of Macao.